A realidade da incorporação de anglicismos - Maria Helena de Moura Neves (Ilha do Desterro)
From the linguistic processing standpoint, this paper analyses aspects of the assimilation of foreignism, especially those of anglicisms, into Brazilian Portuguese. The analysis seeks insertion into the center of the discussion of linguistic politics, as the issue has become a political matter. At the same time it gives importance to the role assimilation plays in covering notions of the semantic structure of Brazilian Portuguese.